Peran Lembaga Rehabilitasi dalam Sistem Hukum Pidana Narkotika di Indonesia - Putri Lidia Damayanti (Pusat Riset dan Inovasi Nasional, 2024)
Addressing narcotics abuse in Indonesia is a complex challenge, with broad impacts on individuals and society. Law no. 35 of 2009 concerning Narcotics provides a legal basis for the rehabilitation of narcotics users as part of the criminal law system, aiming to divert users from punishment to recovery. This research aims to examine the role of rehabilitation institutions in the narcotics criminal law system in Indonesia, including the challenges and effectiveness of its implementation. Analysis shows that even though the rehabilitation policy has been regulated, its implementation still faces obstacles such as limited facilities, lack of consistency in law enforcement, and social stigma which complicates the rehabilitation process and user reintegration into society. In addition, the role of rehabilitation institutions often does not run optimally due to a lack of resources and unclear criteria regarding users who are worthy of rehabilitation.The results of this research emphasize the need for increased rehabilitation facilities, consistent law enforcement, and campaigns to reduce social stigma. With improvements in these various aspects, it is hoped that the role of rehabilitation institutions can become more effective in supporting the recovery of narcotics users and reducing the negative impact of narcotics abuse in Indonesia.